Changes of the state in the commodity economy - Van Y, Nguyen; Giau, Huynh Van; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2024)
The purpose of this article is to clarify the transformation of the state in the commodity economy, including the transformation from class domination to human management, which is the transition process from the division of labor to the regulation and distribution of society by monetary policy. To achieve this purpose, the content is approached from the methods of humanistic philosophy and social philosophy, and at the same time, uses qualitative, analytical, synthetic, and comparative methods, especially the inversion method, to clarify the transformation between the subject and the product in the means and purposes of the existence and development of the state. The results affirm that the state is a product established with a specific historical nature to serve human life. However, when each individual is a product, it carries the instinct of that state, depending on the state. Conclusion: First, the state is a product created by humans, established and produced to serve human life. Second, the state's primary function is to enforce justice, but it becomes the job of civil servants. Third, the function of the state in a commodity economy is to manage and regulate the commodity economic process according to the law and to direct and distribute it by money. Fourth, human rights are the basis for the existence and transformation of the state in a commodity economy.